Impact of a Patient Education Program on Disparities in Kidney Transplant Evaluation - Patzer, Rachel E. (Clin J Am Soc Nephrol, 2012)
BACKGROUND AND OBJECTIVES: In 2007, the Emory Transplant Center (ETC) kidney transplant program implemented a required educational session for ESRD patients referred for renal transplant evaluation to increase patient awareness and decrease loss to follow-up. The purpose of this study was to evaluate the association of the ETC education program on completion of the transplant evaluation process. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Incident, adult ESRD patients referred from 2005 to 2008 were included. Patient data were abstracted from medical records and linked with data from the United States Renal Data System. Evaluation completion was compared by pre- and posteducational intervention groups in binomial regression models accounting for temporal confounding. RESULTS: A total of 1126 adult ESRD patients were examined in two transplant evaluation eras (75% pre- and 25% postintervention). One-year evaluation completion was higher in the post- versus preintervention group (80.4% versus 44.7%, P<0.0001). In adjusted analyses controlling for time trends, the adjusted probability of evaluation completion at 1 year was higher among the intervention versus nonintervention group (risk ratio=1.38, 95% confidence interval=1.12–1.71). The effect of the intervention was stronger among black patients and those patients living in poor neighborhoods (likelihood ratio test for interaction, P<0.05). CONCLUSION: Standardizing transplant education may help reduce some of the racial and socioeconomic disparities observed in kidney transplantation.